Indian Journal of Nematology: Occurrence and Distribution of Meloidogyne incognita Infecting Vegetable Crops in some Districts of Himachal Pradesh, India (Indian Journal of Nematology, 2024)
A total of 353 soil and root samples were collected from 33 different localities of 15 different blocks in Shimla, Sirmaur, Solan, Kangra, and Kinnaur districts of Himachal Pradeshduring 2019–2023. The vegetable crops surveyed included tomato, french bean, pea, potato, capsicum, okra, fodder maize, and mustard. Meloidogyne incognita was encountered in 192 samples out of 353 examined, with a population ranging from 80 to 6400 J2/200 cc of soil. The maximum frequency of occurrence of RKN was recorded in Sirmaur (73.33%), followed by Solan (61.53%), Shimla 48.83%), Kangra (26.66%), and Kinnaur district (14.28%), respectively. The mean value of RGI was highest in Sirmaur (4.5), followed by Solan (3.8), Shimla (3.2), Kangra (2.8), and Kinnaur (1.3), respectively.  The minimum population of M. incognita in the Kinnaur district was observed in the cropping sequence tomato-potato-fodder maize-tomato and in silty to clay loam soil. Whereas the highest nematode population (6400 J2/200 cc soil) was recorded in the cropping sequence tomato-French beans-peas-tomato, which included all the susceptible crops. Furthermore, low populations of M. incognita were recorded in the crop sequences which involved poor hosts in the rotation, such as fodder maize and mustard.